Impact of COVID-19 on the Mental Health of Healthcare Workers: A Cross-Sectional Study From Pakistan - Hayat, Khezar; Arshed, Muhammad; Fiaz, Iqra; Afreen, Urooj; Khan, Faiz Ullah; Khan, Tahir Abbas; Kadirhaz, Muhtar; Shukar, Sundus; Saeed, Azwa; Gill, Muhammad Rouf; Fang, Yu (Frontiers in Public Health, 2021)
Background: The novel coronavirus (COVID-19) pandemic has significantly increased the rate of mortality and morbidity worldwide due to its rapid transmission rate. The mental health status of individuals could have a negative impact attributed to this global situation. Therefore, this study was intended to explore the depression and anxiety prevalence among healthcare workers (HCWs) of Pakistan during the ongoing COVID-19 pandemic. Methods: A cross-sectional survey was undertaken by administering a web-based questionnaire between May 2020 and June 2020. Two tools, including the Patient Health Questionnaire (PHQ9) and Generalized Anxiety Disorder-7 (GAD-7), were employed to measure anxiety and depression among HCWs. The data analyses were carried out using descriptive statistics, Man Whitney and Kruskal Wallis tests. Results: Of 1094 HCWs who participated in this online survey, 742 (67.8%) were physicians, followed by nurses (n=277, 25.3%) and pharmacists (n=75, 6.9%). The survey respondents had a mean depression and anxiety score of 5.49 + 4.22 and 8.32 + 4.28. A considerable number of HCWs (82.2%) utilized online psychological resources to deal with their psychological distress. Female HCWs, physicians, frontline HCWs, and older adults were more likely to suffer from depression and anxiety (p<0.05). Conclusion: During the recent ongoing pandemic of COVID-19, there is a mild level of depression and anxiety among HCWs. Our findings call for urgent psychological interventions for vulnerable groups of HCWs.